First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Protease S of entomopathogenic bacterium Photorhabdus laumondii: expression, purification and effect on greater wax moth Galleria mellonella - Anastasia O. Svetlova; Maria A. Karaseva; Igor M. Berdyshev; Ksenia N. Chukhontseva; Olga V. Pobeguts; Maria A. Galyamina; Igor P. Smirnov; Nikita B. Polyakov; Maria G. Zavialova; Sergey V. Kostrov; Ilya V. Demidyuk (Molecular Biology Reports, 2024)

Analyzing the benefits and limitations of advanced 2,4-D herbicide delivery systems - Vera V. Butova; Tatiana V. Bauer; Vladimir A. Polyakov; Vishnu D. Rajput; Tatiana M. Minkina (Crop Protection, 2024)

Genetic Features of Tongue Cancer Recurrence in Young Adults - E. S. Kolegova; A. A. Schegoleva; R. S. Vorobev; I. K. Fedorova; D. E. Kulbakin; A. P. Polyakov; A. V. Mordovsky; L. P. Yakovleva; A. S. Vyalov; V. T. Tsiklauri; M. A. Kropotov; N. G. Suchkova; et al. (Bulletin of Experimental Biology and Medicine, 2024)

Application of X-ray based modern instrumental techniques to determine the heavy metals in soils, minerals and organic media - Mikhail V. Kirichkov; Vladimir A. Polyakov; Sudhir S. Shende; Tatiana M. Minkina; Dina G. Nevidomskaya; Ming Hung Wong; Tatiana V. Bauer; Victoria A. Shuvaeva; Saglara S. Mandzhieva; Victoria S. Tsitsuashvili (Chemosphere, 2024)

Assessment of the Spatial Resolution and Accuracy of Temperature Measurements in Radiothermometry of the Breast - M. V. Polyakov; A. V. Khoperskov; S. V. Agasieva; I. O. Porokhov (Biomedical Engineering, 2023)

Exploring Five Methods for Estimating Net Community Production on the Siberian Continental Shelf and Slope of the Arctic Ocean - M. B. Alkire; I. Polyakov; R. W. Macdonald (Frontiers in Marine Science, 2022)
The loss of sea ice and changes to vertical stratification in the Arctic Ocean are altering the availability of light and nutrients, with significant consequences for net community production (NCP) and carbon export. However, a general lack of quality data, particular during winter months, inhibits our ability to quantify such change. As a result, two parameters necessary for calculating annual NCP, integration depth (Z int ) and pre-bloom nitrate concentration (N pre ), are often either assigned or estimated from summer measurements. Vertical profiles of temperature, salinity, nitrate, and dissolved oxygen were collected during three cruises conducted between August and October of 2013, 2015, and 2018 in a data-sparse region of the Arctic Ocean along the Siberian continental slope. Estimates of NCP were calculated from these data using five different methods that either assigned constant values for Z int and/or N pre or estimated these parameters from summer observations. The five methods returned similar mean values of Z int (44–54 m), N pre (5.4–5.7 mmol m –3 ), and NCP (12–16 g C m –2 ) across the study region; however, there was considerable variability among stations/profiles. It was determined that the NCP calculations were particularly sensitive to N pre . Despite this sensitivity, mean NCP estimates calculated along four transects re-occupied during the three cruises generally agreed across the five methods with two important exceptions. First, methods with pre-assigned Z int and/or N pre underestimated the NCP when the nitracline shoaled in the Laptev Sea and when high-nutrient shelf waters were advected northward from the East Siberian Sea shelf in 2015. In contrast, the methods that directly estimated both Z int and N pre did not suffer from this bias. These results suggest that assignment of N pre and/or Z int provides reasonable estimates of NCP, particularly averaged over larger spatial scales and/or longer time scales, but these approaches are not suitable for evaluating interannual variability in NCP, particularly in dynamic regions. Combining all methods across the three cruise years indicates NCP in the Laptev Sea and Lomonosov Ridge areas (10–11 g C m –2 ) was slightly lower than that north of Severnaya Zemlya (13 g C m –2 ) and in the East Siberian Sea (16 g C m –2 ).

A Steady Regime of Volume and Heat Transports in the Eastern Arctic Ocean in the Early 21st Century - A. V. Pnyushkov; I. V. Polyakov; G. V. Alekseev; I. M. Ashik; T. M. Baumann; E. C. Carmack; V. V. Ivanov; R. Rember (Frontiers in Marine Science, 2021)
Mooring observations in the eastern Eurasian Basin of the Arctic Ocean showed that mean 2013–2018 along-slope volume and heat (calculated relative to the freezing temperature) transports in the upper 800 m were 4.8 ± 0.1 Sv (1 Sv = 10 6 m 3 /s) and 34.8 ± 0.6 TW, respectively. Volume and heat transports within the Atlantic Water (AW) layer (∼150–800 m) in 2013–2018 lacked significant temporal shifts at annual and longer time scales: averaged over the two periods of mooring deployment in 2013–2015 and 2015–2018, volume transports were 3.1 ± 0.1 Sv, while AW heat transports were 31.3 ± 1.0 TW and 34.8 ± 0.8 TW. Moreover, the reconstructed AW volume transports over longer, 2003–2018, period of time showed strong interannual variations but lacked a statistically significant trend. However, we found a weak positive trend of 0.08 ± 0.07 Sv/year in the barotropic AW volume transport estimated using dynamic ocean topography (DOT) measurements in 2003–2014 – the longest period spanned by the DOT dataset. Vertical coherence of 2013–2018 transports in the halocline (70–140 m) and AW (∼150–800 m) layers was high, suggesting the essential role of the barotropic forcing in constraining along-slope transports. Quantitative estimates of transports and their variability discussed in this study help identify the role of atlantification in critical changes of the eastern Arctic Ocean.

The Pan-Arctic Continental Slope: Sharp Gradients of Physical Processes Affect Pelagic and Benthic Ecosystems - Bodil A. Bluhm; Markus A. Janout; Seth L. Danielson; Ingrid Ellingsen; Maria Gavrilo; Jacqueline M. Grebmeier; Russell R. Hopcroft; Katrin B. Iken; Randi B. Ingvaldsen; Lis L. Jørgensen; Ksenia N. Kosobokova; Ron Kwok; et al. (Frontiers in Marine Science, 2020)
Continental slopes – steep regions between the shelf break and abyssal ocean – play key roles in the climatology and ecology of the Arctic Ocean. Here, through review and synthesis, we find that the narrow slope regions contribute to ecosystem functioning disproportionately to the size of the habitat area (∼6% of total Arctic Ocean area). Driven by inflows of sub-Arctic waters and steered by topography, boundary currents transport boreal properties and particle loads from the Atlantic and Pacific Oceans along-slope, thus creating both along and cross-slope connectivity gradients in water mass properties and biomass. Drainage of dense, saline shelf water and material within these, and contributions of river and meltwater also shape the characteristics of the slope domain. These and other properties led us to distinguish upper and lower slope domains; the upper slope (shelf break to ∼800 m) is characterized by stronger currents, warmer sub-surface temperatures, and higher biomass across several trophic levels (especially near inflow areas). In contrast, the lower slope has slower-moving currents, is cooler, and exhibits lower vertical carbon flux and biomass. Distinct zonation of zooplankton, benthic and fish communities result from these differences. Slopes display varying levels of system connectivity: (1) along-slope through property and material transport in boundary currents, (2) cross-slope through upwelling of warm and nutrient rich water and down-welling of dense water and organic rich matter, and (3) vertically through shear and mixing. Slope dynamics also generate separating functions through (1) along-slope and across-slope fronts concentrating biological activity, and (2) vertical gradients in the water column and at the seafloor that maintain distinct physical structure and community turnover. At the upper slope, climatic change is manifested in sea-ice retreat, increased heat and mass transport by sub-Arctic inflows, surface warming, and altered vertical stratification, while the lower slope has yet to display evidence of change. Model projections suggest that ongoing physical changes will enhance primary production at the upper slope, with suspected enhancing effects for consumers. We recommend Pan-Arctic monitoring efforts of slopes given that many signals of climate change appear there first and are then transmitted along the slope domain.

An Optimized k-Space Configuration for Parallel MRI Reconstruction - M. A. Pugachevskii; A. G. Polyakov (Biomedical Engineering, 2020)

Peculiarities of Pharmacokinetics and Bioavailability of Some Cardiovascular Drugs under Conditions of Antiorthostatic Hypokinesia - A. V. Polyakov; A. A. Svistunov; S. N. Kondratenko; I. V. Kovachevich; L. G. Repenkova; M. I. Savelyeva; V. G. Kukes (Bulletin of Experimental Biology and Medicine, 2020)

A Framework for the Development, Design and Implementation of a Sustained Arctic Ocean Observing System - Craig M. Lee; Sandy Starkweather; Hajo Eicken; Mary-Louise Timmermans; Jeremy Wilkinson; Stein Sandven; Dmitry Dukhovskoy; Sebastian Gerland; Jacqueline Grebmeier; Janet M. Intrieri; Sung-Ho Kang; Molly McCammon; et al. (Frontiers in Marine Science, 2019)

Prognostic Risk Models for the Development of Cardiovascular Dysfunction in Adolescents with Essential Hypertension - A. S. Kosovtseva; Т. А. Bairova; L. V. Rychkova; V. M. Polyakov; L. I. Kolesnikova (Bulletin of Experimental Biology and Medicine, 2019)

Heat, salt, and volume transports in the eastern Eurasian Basin of the Arctic Ocean from 2 years of mooring observations - Andrey V. Pnyushkov; Igor V. Polyakov; Robert Rember; Vladimir V. Ivanov; Matthew B. Alkire; Igor M. Ashik; Till M. Baumann; Genrikh V. Alekseev; Arild Sundfjord (Ocean Science, 2018)
This study discusses along-slope volume, heat, and salt transports derived from observations collected in 2013–2015 using a cross-slope array of six moorings ranging from 250 to 3900 m in the eastern Eurasian Basin (EB) of the Arctic Ocean. These observations demonstrate that in the upper 780 m layer, the along-slope boundary current advected, on average, 5.1±0.1 Sv of water, predominantly in the eastward (shallow-to-right) direction. Monthly net volume transports across the Laptev Sea slope vary widely, from ∼0.3±0.8 in April 2014 to ∼9.9±0.8 Sv in June 2014; 3.1±0.1 Sv (or 60 %) of the net transport was associated with warm and salty intermediate-depth Atlantic Water (AW). Calculated heat transport for 2013–2015 (relative to −1.8 ∘C) was 46.0±1.7 TW, and net salt transport (relative to zero salinity) was 172±6 Mkg s−1. Estimates for AW heat and salt transports were 32.7±1.3 TW (71 % of net heat transport) and 112±4 Mkg s−1 (65 % of net salt transport). The variability of currents explains ∼90 % of the variability in the heat and salt transports. The remaining ∼10 % is controlled by temperature and salinity anomalies together with the temporal variability of the AW layer thickness. The annual mean volume transports decreased by 25 % from 5.8±0.2 Sv in 2013–2014 to 4.4±0.2 Sv in 2014–2015, suggesting that changes in the transports at interannual and longer timescales in the eastern EB may be significant.

Comparative Study of Novel Fluorescent Cyanine Nucleotides: Hybridization Analysis of Labeled PCR Products Using a Biochip - V. E. Shershov; S. A. Lapa; V. E. Kuznetsova; M. A. Spitsyn; T. O. Guseinov; S. A. Polyakov; A. A. Stomahin; A. S. Zasedatelev; A. V. Chudinov (Journal of Fluorescence, 2017)

How economics can further the success of ecological restoration - Md Sayed Iftekhar; Maksym Polyakov; Dean Ansell; Fiona Gibson; Geoffrey M. Kay (Conservation Biology, 2017)
Restoration scientists and practitioners have recently begun to include economic and social aspects in the design and investment decisions for restoration projects. With few exceptions, ecological restoration studies that include economics focus solely on evaluating costs of restoration projects. However, economic principles, tools, and instruments can be applied to a range of other factors that affect project success. We considered the relevance of applying economics to address 4 key challenges of ecological restoration: assessing social and economic benefits, estimating overall costs, project prioritization and selection, and long‐term financing of restoration programs. We found it is uncommon to consider all types of benefits (such as nonmarket values) and costs (such as transaction costs) in restoration programs. Total benefit of a restoration project can be estimated using market prices and various nonmarket valuation techniques. Total cost of a project can be estimated using methods based on property or land‐sale prices, such as hedonic pricing method and organizational surveys. Securing continuous (or long‐term) funding is also vital to accomplishing restoration goals and can be achieved by establishing synergy with existing programs, public–private partnerships, and financing through taxation.

Production and Analysis of Biological Properties of Recombinant Human Apolipoprotein A-I - A. V. Ryabchenko; M. V. Kotova; N. V. Tverdohleb; R. A. Knyazev; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2015)

Content of Circulating Extracellular DNA, Plasma Activities of Matrix Metalloproteinases, and Ultrastructure of the Myocardium in Hypothyroid Rats with Hypercholesterolemia - L. M. Polyakov; E. L. Lushnikova; A. A. Karpova; G. S. Russkikh; O. N. Poteryaeva; D. B. Nikityuk; L. M. Nepomnyashchikh; Zh. I. Belonogova; D. V. Sumenkova; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2015)

Characterizing Spatial Uncertainty when Integrating Social Data in Conservation Planning - A. M. Lechner; C. M. Raymond; V. M. Adams; M. Polyakov; A. Gordon; J. R. Rhodes; M. Mills; A. Stein; C. D. Ives; E. C. Lefroy (Conservation Biology, 2014)
Recent conservation planning studies have presented approaches for integrating spatially referenced social (SRS) data with a view to improving the feasibility of conservation action. We reviewed the growing conservation literature on SRS data, focusing on elicited or stated preferences derived through social survey methods such as choice experiments and public participation geographic information systems. Elicited SRS data includes the spatial distribution of willingness to sell, willingness to pay, willingness to act, and assessments of social and cultural values. We developed a typology for assessing elicited SRS data uncertainty which describes how social survey uncertainty propagates when projected spatially and the importance of accounting for spatial uncertainty such as scale effects and data quality. These uncertainties will propagate when elicited SRS data is integrated with biophysical data for conservation planning and may have important consequences for assessing the feasibility of conservation actions. To explore this issue further, we conducted a systematic review of the elicited SRS data literature. We found that social survey uncertainty was commonly tested for, but that these uncertainties were ignored when projected spatially. Based on these results we developed a framework which will help researchers and practitioners estimate social survey uncertainty and use these quantitative estimates to systematically address uncertainty within an analysis. This is important when using SRS data in conservation applications because decisions need to be made irrespective of data quality and well characterized uncertainty can be incorporated into decision theoretic approaches.

A Multidisciplinary Conceptualization of Conservation Opportunity - KATIE MOON; VANESSA M. ADAMS; STEPHANIE R. JANUCHOWSKI‐HARTLEY; MAKSYM POLYAKOV; MORENA MILLS; DUAN BIGGS; ANDREW T. KNIGHT; EDWARD T. GAME; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
An opportunity represents an advantageous combination of circumstances that allows goals to be achieved. We reviewed the nature of opportunity and how it manifests in different subsystems (e.g., biophysical, social, political, economic) as conceptualized in other bodies of literature, including behavior, adoption, entrepreneur, public policy, and resilience literature. We then developed a multidisciplinary conceptualization of conservation opportunity. We identified 3 types of conservation opportunity: potential , actors remove barriers to problem solving by identifying the capabilities within the system that can be manipulated to create support for conservation action; traction , actors identify windows of opportunity that arise from exogenous shocks, events, or changes that remove barriers to solving problems; and existing , everything is in place for conservation action (i.e., no barriers exist) and an actor takes advantage of the existing circumstances to solve problems. Different leverage points characterize each type of opportunity. Thus, unique stages of opportunity identification or creation and exploitation exist: characterizing the system and defining problems; identifying potential solutions; assessing the feasibility of solutions; identifying or creating opportunities; and taking advantage of opportunities. These stages can be undertaken independently or as part of a situational analysis and typically comprise the first stage, but they can also be conducted iteratively throughout a conservation planning process. Four types of entrepreneur can be identified (business, policy, social, and conservation), each possessing attributes that enable them to identify or create opportunities and take advantage of them. We examined how different types of conservation opportunity manifest in a social–ecological system (the Great Barrier Reef) and how they can be taken advantage of. Our multidisciplinary conceptualization of conservation opportunity strengthens and legitimizes the concept.

Redox Status as a Metabolic Stage, Integrating Emotional Pattern and Blood Pressure in Adolescents - L. I. Kolesnikova; Zh. V. Prokhorova; B. Ya. Vlasov; V. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2014)

Heat loss from the Atlantic water layer in the northern Kara Sea: causes and consequences - I. A. Dmitrenko; S. A. Kirillov; N. Serra; N. V. Koldunov; V. V. Ivanov; U. Schauer; I. V. Polyakov; D. Barber; M. Janout; V. S. Lien; M. Makhotin; Y. Aksenov (Ocean Science, 2014)
A distinct, subsurface density front along the eastern St. Anna Trough in the northern Kara Sea is inferred from hydrographic observations in 1996 and 2008–2010. Direct velocity measurements show a persistent northward subsurface current (~ 18 cm s−1) along the St. Anna Trough eastern flank. This sheared flow, carrying the outflow from the Barents and Kara seas to the Arctic Ocean, is also evident from shipboard observations as well as from geostrophic velocities and numerical model simulations. Although we cannot substantiate our conclusions by direct observation-based estimates of mixing rates in the area, we hypothesize that the enhanced vertical mixing along the St. Anna Trough eastern flank favors the upward heat loss from the intermediate warm Atlantic water layer. Modeling results support this hypothesis. The upward heat flux inferred from hydrographic data and model simulations is of O(30–100) W m−2. The region of lowered sea ice thickness and concentration seen both in sea ice remote sensing observations and model simulations marks the Atlantic water pathway in the St. Anna Trough and adjacent Nansen Basin continental margin. In fact, the sea ice shows a delayed freeze-up onset during fall and a reduction in the sea ice thickness during winter. This is consistent with our results on the enhanced Atlantic water heat loss along the Atlantic water pathway in the St. Anna Trough.

Comparison of different techniques in atmospheric temperature-humidity sensing from space - Alexander Polyakov; Yurii M. Timofeyev; Yana Virolainen (International Journal of Remote Sensing, 2014)

Apolipoprotein A-I as a Carrier of Lipopolysaccharide into Rat Hepatocytes - D. V. Sumenkova; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2013)

Structural Changes in the Myocardium and Serum Lipid Spectrum in Experimental Hypercholesterolemia and Hypothyroidism - L. M. Nepomnyashchikh; E. L. Lushnikova; L. P. Polyakov; O. P. Molodykh; M. G. Klinnikova; G. S. Russkikh; O. N. Poteryaeva; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2013)

The Brain’s Error-Detecting Mechanism – a PET Study - M. V. Kireev; A. D. Korotkov; Yu. I. Polyakov; A. D. Anichkov; S. V. Medvedev (Neuroscience and Behavioral Physiology, 2013)

Activity of Matrix Metalloproteinases during Antimycobacterial Therapy in Mice with Simulated Tuberculous Inflammation - D. V. Sumenkova; G. S. Russkikh; O. N. Poteryaeva; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2013)

Plasma Lipoproteins as a Transport Form of Extracellular DNA - D. V. Sumenkova; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2013)

High-pressure neutron diffraction study on H–D isotope effects in brucite - Juske Horita; António M. dos Santos; Christopher A. Tulk; Bryan C. Chakoumakos; Veniamin B. Polyakov (Physics and Chemistry of Minerals, 2010)

Effect of Apolipoprotein A-I Complex with Tetrahydrocortisone on Protein Biosynthesis and Glucose Absorption by Rat Hepatocytes - D. V. Sumenkova; R. A. Knyazev; R. S. Guschya; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2009)

A New Genetic Variant of MDX Mice: Study of the Phenotype - L. I. Krivov; M. A. Stenina; V. N. Yarygin; A. V. Polyakov; V. I. Savchuk; S. A. Obrubov; N. V. Komarova (Bulletin of Experimental Biology and Medicine, 2009)

Effect of Plasma Lipoproteins and Their Complexes with Polysaccharides on Interleukin-1β Concentration in Macrophages of Mice with HA-1 Ascitic Hepatoma - L. M. Polyakov; D. V. Sumenkova; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2009)

Modification and clearance of low density lipoproteins during the formation of endotoxin-lipoprotein complexes - Ya. Sh. Schvartz; L. M. Polyakov; M. I. Dushkin; E. N. Pivovarova (Bulletin of Experimental Biology and Medicine, 2008)

Interaction of apolipoproteins A-I and E in the regulation of DNA, RNA, and protein biosynthesis in cultured rat hepatocytes - L. E. Panin; D. V. Sumenkova; R. A. Knyazev; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2007)

Effect of complexes of apolipoprotein A-I with tetrahydrocortisol and pregnenolone on protein biosynthesis in rat hepatocytes culture - L. E. Panin; R. A. Knyazev; D. V. Sumenkova; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2007)

Identification of all pachytene bivalents in the common shrew using DAPI-staining of synaptonemal complex spreads - N. M. Belonogova; T. V. Karamysheva; L. S. Biltueva; E. A. Perepelov; J. M. Minina; A. V. Polyakov; N. S. Zhdanova; N. B. Rubtsov; J. B. Searle; P. M. Borodin (Chromosome Research, 2006)

The Use of Homeopathic Preparation Vozraston in the Therapy of Patients with Rheumatoid Arthritis - S. M. Noskov; A. V. Snigireva; L. N. Dolgova; M. A. Somova; D. P. Polyakov (Bulletin of Experimental Biology and Medicine, 2003)

Development and Clinical Experience with a Computer Monitoring System Used at the Intensive Cardiological Care Unit - N. I. Kalyadin; V. A. Lemenkov; A. V. Korobeinikov; S. M. Perevozchikov; E. G. Odiyankov; A. N. Rodionov; V. F. Polyakov; S. M. Kotkov (Biomedical Engineering, 2002)

Effects of apolipoproteins C on oxidative phosphorylation in rat liver mitochondria - L. E. Panin; N. I. Shalbueva; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2000)

Effects of apolipoproteins C on oxidative phosphorylation in rat liver mitochondria - L. E. Panin; N. I. Shalbueva; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2000)

Blood concentration of apolipoproteins A-1, B, and E after intensive physical load and during recovery period - L. E. Panin; O. N. Poteryaeva; N. V. Atuchina; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 1998)